Virtual Private Networks – Based Home System - Volner, R.; Smrž, V. (Elektronika ir Elektrotechnika, 2009)
The term security network intelligence is widely used in the field of communication security network. A number of new and potentially concepts and products based on the concept of security network intelligence have been introduced, including smart flows, intelligent routing, and intelligent web switching. Many intelligent systems focus on a specific security service, function, or device, and do not provide true end-to-end service network intelligence. True security network intelligence requires more than a set of disconnected elements, it requires an interconnecting and functionally coupled architecture that enables the various functional levels to interact and communicate with each other. Ill. 3, bibl. 10 (in English; abstracts in English, Russian and Lithuanian).